Climate variability and the adaptive capacity of the rural farmers: The case of Matobo District- Zimbabwe 2016 to 2017 rainy season - Funteh, Mark Bolak; Ncube, Annamary (IJRDO - Journal of Social Science and Humanities Research, 2019)
This paper evaluates the adaptive capacity of rural farmers in the midst of climate variability in 2016 to 2017 rainy season in Matobo district. Climate variability has emerged as a major global crisis of the 21st century because of its past, present and projected environmental and socio-economic impacts. The shift in climatic conditions over the Sub-Saharan Region towards semi-arid to arid conditions has stemmed up a lot of concern as to whether Africa can adapt well to these climatic conditions. The past three decades have been characterized by an erratic rainfall pattern over Africa’s sub-tropics and a significant decline in the amount of rainfall. This has resulted in droughts which have significantly affected agriculture and food production. Crops have failed to quickly adapt to these harsh climatic conditions. Research on the impacts of climate variability in Zimbabwe shows that the country’s agricultural sector is already suffering from changing rainfall pattern. In as much climate variability is affecting everyone directly or indirectly, farmers worldwide are at the forefront. This is mainly because their livelihoods are mostly hit by ever changing climate variations. Some research have shown the adaptation strategies that farmers have employed as a result of variations in rainfall and temperatures patterns. Mostly in Matobo district, these variations of rainfall and temperature patterns are mainly low rainfall and high temperature for the past decades with the exception of year 2011 and 2012 which experienced moderate rainfall during the rainy season. As a result of these climatic conditions in the district of low rainfall and high temperature patterns that were easy predicated even by farmers, farmers had developed innovations with institutions to curb low rains which were being experienced in the district. However, 2016 to 2017 rainy season posed a change in climatic conditions in the district. The district experienced heavy rains throughout the season. As a result of this climatic variation of 2016 to 2017 rainy season, this paper seek to evaluate how farmers in Matobo district were able to adapt to this change as they were mainly used to low rainfall patterns and have further developed adaptive strategies to curb low rains in the district. This papers will highlight the effects of high rainfall patterns on farmers crops, the adaptive capacity of farmers to high rainfall of 2016 to 2017 rainy season and asses the role of institutions towards the adaptive capacity of farmers.